EFFECT OF FIRM SIZE AND PROFITABILITY TOWARD SOCIAL DISCLOSURE - Fudji Sri Mar'ati; Erna Sudarmawanti; Tasya Embun Khatulistiwa (Jurnal Ekonomi, 2023)
The purpose of this study is to determine whether firm size and profitability affect social disclosure. The population of this study is LQ45 companies listed on the Indonesia Stock Exchange. The research sample is LQ 45 companies that remain in the LQ 45 company category for the listing period, namely: the period August 2020 – January 2021, the period February 2021 – July 2021 and the period August 2021 – January 2022. The analysis tool used is SEM-PLS (Structural Equation Modeling based on Partial Least Square). The test results show that firm size has a positive and significant effect on social disclosure. However, profitability has a negative and significant effect on social disclosure.